2012
DOI: 10.1152/ajprenal.00624.2011
|View full text |Cite
|
Sign up to set email alerts
|

Renal actions of atrial natriuretic peptide in spontaneously hypertensive rats: the role of nitric oxide as a key mediator

Abstract: Atrial natriuretic peptide (ANP) is an important regulator of blood pressure (BP). One of the mechanisms whereby ANP impacts BP is by stimulation of nitric oxide (NO) production in different tissues involved in BP control. We hypothesized that ANP-stimulated NO is impaired in the kidneys of spontaneously hypertensive rats (SHR) and this contributes to the development and/or maintenance of high levels of BP. We investigated the effects of ANP on the NO system in SHR, studying the changes in renal nitric oxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In previous studies we demonstrated that male SHR showed increased urinary excretion of NO metabolites and augmented activity of cardiovascular and renal NOS compared to normotensive animals, indicating that the NO pathway is up-regulated in this model of hypertension [15], [33]. In the present study, we showed that female SHR exhibit lower SBP than male SHR.…”
Section: Discussionsupporting
confidence: 68%
“…In previous studies we demonstrated that male SHR showed increased urinary excretion of NO metabolites and augmented activity of cardiovascular and renal NOS compared to normotensive animals, indicating that the NO pathway is up-regulated in this model of hypertension [15], [33]. In the present study, we showed that female SHR exhibit lower SBP than male SHR.…”
Section: Discussionsupporting
confidence: 68%
“…37,38,44,45 In addition, NPR-C activation by C-ANP 4-23 was also reported to activate eNOS in various tissues including smooth muscle. 33 We also examined whether C-ANP 4-23 -induced attenuation of BP in SHRs is attributed to its ability to augment the levels of eNOS and NO; however, in the present in vivo study, we demonstrate that C-ANP 4-23 treatment decreased the enhanced levels of NO and eNOS in kidney and attenuated further the decreased levels of eNOS and NO in VSMC and aorta from SHRs and suggest that C-ANP 4-23 -induced decreased BP may not involve NO and NO-stimulated cGMP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with the studies of other investigators who have demonstrated an enhanced expression of iNOS (inducible nitric oxide synthase) and eNOS and an elevation of renal NOS activity in 12-week-old SHRs 52 and 20-week-old SHRs compared with WKY. 53 In addition, Elesgaray et al 38 have shown the overexpression of all the 3 isoforms, eNOS, iNOS, and nNOS (neuronal nitric oxide synthase), in kidney from SHRs compared with WKY rats. Thus taken together, it may be suggested that the upregulation of NOS isoforms in kidney may not contribute to the development of high BP and may play a compensatory role in response to an increased BP in SHRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, chronic treatment with ANP decreased SBP and increased sodium and water excretion. In previous studies we found that these actions of ANP involved, at least in part, an increase in renal NOS activity by interacting with natriuretic receptors NPR-A and NPR-C in both normotensive and hypertensive male animals [33]. …”
Section: Discussionmentioning
confidence: 99%